2021
DOI: 10.1123/mc.2020-0052
|View full text |Cite
|
Sign up to set email alerts
|

Restoring Walking Complexity in Older Adults Through Arm-in-Arm Walking: Were Almurad et al.’s (2018) Results an Artifact?

Abstract: The analysis of stride series revealed a loss of complexity in older people, which correlated with the falling propensity. A recent experiment evidenced an increase of walking complexity in older participants when they walked in close synchrony with a younger companion. Moreover, a prolonged experience of such synchronized walking yielded a persistent restoration of complexity. This result, however, was obtained with a unique healthy partner, and it could be related to a particular partner’s behavior. The auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
(41 reference statements)
1
1
0
Order By: Relevance
“…They observed a restoration of complexity in the older participants after three weeks, and this effect persisted two weeks after the end of the training session. These results were further confirmed in another study with different participants [ 27 ]. Although these results are promising, the restoration of a healthy complex gait does not necessarily imply a relevant improvement in the motor function.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…They observed a restoration of complexity in the older participants after three weeks, and this effect persisted two weeks after the end of the training session. These results were further confirmed in another study with different participants [ 27 ]. Although these results are promising, the restoration of a healthy complex gait does not necessarily imply a relevant improvement in the motor function.…”
Section: Introductionsupporting
confidence: 78%
“…The general idea of this research project is to confirm the results of Almurad et al [26,27] in a larger sample. The main modification to Almurad's protocol is that the "gait teacher" during arm-in-arm walking will be a younger person (different for each older participant) rather than a member of the study staff (the same for each older participant).…”
Section: Rationale and Objectivesmentioning
confidence: 83%
“…The estimation of the H exponent has become very relevant in the fields of health and aging because this fractal structure tends to diminish or even disappear with the first signs of age or disease, making the exponent H a very promising predictor. We (Almurad et al, 2017;Almurad et al, 2018;Ezzina et al, 2021) have also suggested, through several studies, that it was possible to restore complexity in older adults. However, all the participants in our studies were characterized by healthy aging and did not have any motor disability limiting their movements.…”
Section: Introductionmentioning
confidence: 94%